Implementasi Peraturan Pemerintah Nomor 22 Tahun 2021 Tentang Penyelenggaraan Perlindungan Dan Pengelolaan Lingkungan Hidup Dalam Pengendalian Pencemaran Limbah Cair PT. Evergreen Di Tanjung Morawa Perspektif Siyasah Dusturiyah - Triana, Tanty; Matondang, Maulidya Mora (Lex Stricta : Jurnal Ilmu Hukum, 2025)
This study aims to examine the implementation of Government Regulation No. 22 of 2021 on the Management and Protection of the Environment in controlling liquid waste by PT. Evergreen Tanjung Morawa, analyzed from the perspective of Siyasah Dusturiyah. The research employs a juridical-empirical approach, utilizing interviews, observations, and documentation as data collection techniques. The findings reveal that waste management practices have not fully complied with the regulatory framework due to weak supervision, limited institutional capacity, and low industrial commitment to environmental protection. Consequently, water pollution, health problems, and declining local economic productivity have occurred. In the framework of Fiqh Siyasah Dusturiyah, the government bears legal and moral responsibility to ensure public welfare based on the principles of Maqāṣid al-Syarī‘ah and al-Mas’uliyyah al-Bi’iyyah (ecological responsibility). The study recommends strengthening a supervision system grounded in Islamic ethical values to promote just and sustainable environmental governance.